waking wp : with everyone around us - Steiner, Tej, ....- (Ashland Oregon : Hart Circle Network, 2017)
A step-by-by guide, a book of poetry, a memoir, a life's work all blended together to form an alive manuscript for how we can support one another in Heart Awakening and co-creating a Culture of Connection. In the past, only a handful of people awakened during any given era. Today, there are millions of people awakening all at once. This is new. Something else is new. You and I are included in the millions of people awakening. The timing for our collective bloom couldn’t be better. More than anything else, our planet has a rising fever and requires unprecedented cooperation to bring her temperature down. Our survival depends upon our awakening together. This book is about Heart Awakening, but not in the way you might expect. Instead of presenting some new or old way to awaken individually, I'm sharing specific, reliable ways we can change our existing friendships, families and organizations so that they support us in Heart Awakening rather than hinder us. This book is a guide or blueprint showing one way in which we can do this.
Keywords: Heart awakening